Pengaruh Media Power Point Terhadap Minat dan Pemahaman Konsep Pada Mata Pelajaran IPAS Siswa Kelas V SD Negeri 011 Bukit Gajah - Untung Sugiarto; Ramdhan Witarsa; Musnar Indra Daulay (Journal of Innovation in Teaching and Instructional Media, 2026)
This study aims to determine the effect of using PowerPoint media on students' learning interest and conceptual understanding in the IPAS subject for fifth-grade students at SD Negeri 011 Bukit Gajah. The research was motivated by the low levels of student interest and conceptual understanding due to the continued use of conventional teaching methods and lack of engaging instructional media. The study employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The subjects consisted of two classes: an experimental class using PowerPoint media and a control class using picture media. Instruments included a questionnaire to measure learning interest and a test to assess conceptual understanding. The results showed that the use of PowerPoint media significantly improved both student interest and conceptual understanding. Thus, PowerPoint media can serve as an effective alternative to enhance the quality of IPAS instruction in elementary schools.